Patient Satisfaction in the Inpatient Room of the Management Board of Arifin Nu'mang General Hospital - Imran, Ali; Mahendika, Devin; Rante, Anshar; Fredy Saputra, M Khalid; Briliannita, Anjar; Ajeng Wijayanti, Lumastari; Nurhaedah, Nurhaedah (International Journal of Health Sciences, 2023)
Patient satisfaction with the health services provided is influenced by satisfaction with services (medical, nursing, nutrition, laboratory, radiology, administration), environment and facilities available. The better the health services provided by a hospital, the more satisfying the patient as a service recipient is expected, although basically client satisfaction with the services provided is a subjective value of the quality of service provided and received by the client. Although this subjective value is strongly influenced by various factors, client satisfaction will still be based on the truth and objective reality experienced by clients when receiving services at the Hospital. The purpose of this study is to determine the factors that affect patient satisfaction in the inpatient room of the Arifin Nu'mang General Hospital Management Agency. The type of research used is descriptive research, which explains something or some circumstances (Azwar & Prihartono, 2013). This study uses a cross sectional design that reveals the relationship between the independent variable and the dependent variable (Nursalam & Pariani, 2001). This study was conducted to see Analyst factors affecting patient satisfaction in the inpatient room of Arifin Nu'mang Regency General Hospital Management Agency. The result is After data collection and analysis of existing data, it can be seen that in general patients in the Inpatient Room of the Management Board of the Arifin Nu'mang General Hospital said they were satisfied with the services provided. This can be seen in the data that 90% of respondents said they were satisfied and only 10% were not satisfied. The conclusion of this study is that there is a significant relationship between hospital services and patient satisfaction in the inpatient room of Arifin Nu'mang General Hospital Management Agency.